Particularities of determining primary energy needs for building materials/Pirminės energijos poreikių statybinėms medžiagoms nustatymo ypatumai - Čiuprinskas, Kęstutis; Martinaitis, Vytautas (Journal of Civil Engineering and Management, 1997)
Civil buildings in Lithuania consume one half of final energy or about 70% of heat generated in thermoelectric and heat power stations. However, energy is necessary not only for exploitation but also for the creation of buildings: manufacture of building materials, transportation and construction. For global energy saving in the construction industry, at the state level, it is important to determine an optimum ratio between energy requirement for building creation and exploitation. Taking into account the durability of buildings for the evaluation of strategic relation ships between energetics and construction industry it is reasonable to use a physical building life cycle energy requirement model, because the reliability of an economical prognosis is usually lower than that in physical processes. In this work generalised ratios are suggested for energy requirement by the main building materials, which can be used in the calculation of a physical building life cycle model. In collecting this information three sources were used, namely: from Lithuania, former USSR and Western countries. In the beginning we hoped that the collected information would show higher energy needs for the production of building materials in Lithuania and other former USSR countries than those in developed countries, where manufacturing technology is more modern, and energy saving measures have been implemented earlier. After collecting more data, it was evident from foreign—literature that in Western countries the energy needs are bigger because they are based on other energy needs estimation levels. In the estimation data of energy needs for the Lithuanian building materials industry the levels of technological processes are not clearly described. In this case an application of such data for a physical model of life cycle cost estimations cannot be used directly. For a more detailed analysis 10 building materials were chosen: silicate brick, ceramic brick, rockwool, polyctirol, cement, timber, steel, glass, concrete, ferro-concrete. Energy requirements are classified according to 4 levels of full technological processes, i.e.: for the main process, for raw materials, for machines and for machines that produce these machines. Taking into account the indetermination of the information of data sources, the values can be recommended only for a tentative evaluation. More precise values can be obtained by a detailed analysis of the Lithuanian industry. For building construction industry prognosis one monitoring for building and insulation material manufacturing processes is necessary taking into account different technological levels and processes. Article in Lithuanian. First Published Online: 26 Jul 2012